2006
DOI: 10.1007/s10549-006-9234-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Expression in Benign Breast Ductal Cells Obtained from Random Periareolar Fine Needle Aspiration Correlates with Menopausal Status and Cytomorphology Index Score

Abstract: ER can be readily measured in cytologic specimens obtained by RPFNA with the use of antigen retrieval method. Further, ER expression in cytologic specimens is influenced by postmenopausal status and morphologic abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Until now rFNA samples have been used for immunohistochemistry (27,28) and DNA-based analyses (29)(30)(31)(32)(33)(34), although feasibility of gene expression measurement has been explored (35). Considering the topographic heterogeneity in the breast, rFNA sampling is a useful tool for the discovery of breast cancer risk biomarkers; it provides a predominantly epithelial sample from a large area of the breast and allows the evaluation of women with clinically normal breasts, therefore greatly expanding the population for study, and eventual application of results.…”
Section: Discussionmentioning
confidence: 99%
“…Until now rFNA samples have been used for immunohistochemistry (27,28) and DNA-based analyses (29)(30)(31)(32)(33)(34), although feasibility of gene expression measurement has been explored (35). Considering the topographic heterogeneity in the breast, rFNA sampling is a useful tool for the discovery of breast cancer risk biomarkers; it provides a predominantly epithelial sample from a large area of the breast and allows the evaluation of women with clinically normal breasts, therefore greatly expanding the population for study, and eventual application of results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that E 2 stimulates cell proliferation in an ER α -dependent manner with accumulation of genetic damage leading to carcinogenesis [21]. Furthermore, ER α expression levels have been correlated with breast cancer risk in postmenopausal women [22]. Despite these interesting correlative findings on the oncogenic effects of estrogen, the genetic factors and their signaling pathways involved in the process have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ki-67 and ER expression appear to increase with increasing morphologic abnormality in both histologic and RPFNA specimens [14,46,47]. Further, a cross-sectional study of women with hyperplasia in benign biopsies showed higher Ki-67 (median 3.8%) and ER (median 57%) in patients ultimately progressing to cancer than in controls which did not (medians of 0.8% for Ki-67 and 30% for ER, respectively) [48].…”
Section: Intra-epithelial Neoplasia As a Risk Biomarkermentioning
confidence: 92%
“…First, it allows direct assessment of pre-cancerous change presuming a field effect. In addition to morphology, material is available for other response markers such as Ki-67 and ER, both of which increase in expression with increasing cytomorphologic abnormality [46,47]. Despite the fact that this is an invasive procedure there is minimal discomfort with a median pain score of 1 (reviewed in [41]).…”
Section: Phase II Trialsmentioning
confidence: 99%